Inquiry Learning on History Materials to Improve Critical Thinking of Grade XI Students - Wijayanti, Ratna Dwi; Fajriyah, Izzatul; Aziz, M. Faris Abdil; Widodo, J. Priyanto (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research explores the application of inquiry learning model in history subject at SMK PGRI 2 Sidoarjo to improve critical thinking skills of grade XI students. Using qualitative methods, the research involved observation, interviews and document analysis. The results show that careful planning, educator training and integration of relevant learning resources support the success of this method. Learners became more active, able to ask in-depth questions, and develop arguments based on historical evidence. This study is able to strengthen the literature on the effectiveness of inquiry learning methods and provides practical and theoretical implications for educators. Further research using a wider sample is needed to strengthen these findings.